Immune Mechanisms Underlying Hepatitis B Surface Antigen Seroclearance in Chronic Hepatitis B Patients With Viral Coinfection - Wu, Shuling; Yi, Wei; Gao, Yuanjiao; Deng, Wen; Bi, Xiaoyue; Lin, Yanjie; Yang, Liu; Lu, Yao; Liu, Ruyu; Chang, Min; Shen, Ge; Hu, Leiping; et al. (Frontiers in Immunology, 2022)
It is considered that chronic hepatitis B patients have obtained functional cure if they get hepatitis B surface antigen (HBsAg) seroclearance after treatment. Serum HBsAg is produced by cccDNA that is extremely difficult to clear and dslDNA that is integrated with host chromosome. High HBsAg serum level leads to failure of host immune system, which makes it unable to produce effective antiviral response required for HBsAg seroclerance. Therefore, it is very difficult to achieve functional cure, and fewer than 1% of chronic hepatitis B patients are cured with antiviral treatment annually. Some chronic hepatitis B patients are coinfected with other chronic viral infections, such as HIV, HCV and HDV, which makes more difficult to cure. However, it is found that the probability of obtaining HBsAg seroclearance in patients with coinfection is higher than that in patients with HBV monoinfection, especially in patients with HBV/HIV coinfection who have an up to 36% of HBsAg 5-year-seroclerance rate. The mechanism of this interesting phenomenon is related to the functional reconstruction of immune system after antiretroviral therapy (ART). The quantity increase and function recovery of HBV specific T cells and B cells, and the higher level of cytokines and chemokines such as IP-10, GM-CSF, promote HBsAg seroclearance. This review summarizes recent studies on the immune factors that have influence on HBsAg seroconversion in the chronic hepatitis B patients with viral coinfection, which might provide new insights for the development of therapeutic approaches to partially restore the specific immune response to HBV and other viruses.